Service Innovation for Family Development for Toddlers at the Extension Center for Planning Family Planning Services - Hery Nariyah; Darwanto Darwanto; Moh Sutarjo (LPPM of NAROTAMA UNIVERSITY, 2021)
Not yet optimal Family Development Program for Toddlers at the DPPKBP3 Extension Center, Kedawung District, Cirebon Regency, Lack of Family Planning Extension officers Lack of facilities and infrastructure to support the Toddler Family Development Program (BKB). The Regional Government establishes a family development policy through fostering family welfare resilience, one of which is carried out by means of: The BKB program as a part of the Family Planning (KB) program aims to increase the knowledge and skills of parents and other family members in fostering growth and development of children under five through physical stimulation, motor intelligence, emotional from socioeconomic as well as possible is one of the efforts to be able to develop family functions. Armed with this knowledge and skills, it is hoped that parents will be able to educate and nurture their toddlers from an early age so that these children can grow and develop into quality Indonesian human beings. The research method used is a qualitative research method. The results showed that the factors that influence the Policy for the Community Development Program for Toddlers at the DPPKBP3 Extension Center, Kedawung District, Cirebon Regency are communication, resources, disposition and bureaucratic structure.